Cross Cultural Indicators of Independent Learning in Young Children: A Jordanian Case. (10th June 2016) - Almeqdad, Qais; Al-Hamouri, Firas; Zghoul, Rafe'a A.; Al-Rousan, Ayoub; Whitebread, David
Abstract: This study attempts to explore the level of Independent Learning (IL) amongst a sample of Jordanian preschoolers. Behaviors of sixty preschool children aged 5–6 years old were observed and rated by their teachers against an Arabic version of the Children's Independent Learning Development (CHILD 3–5) observational instrument to explore the independent learning among young children according to their gender, engagement level, parental education and the size of their families. The results illustrated that preschoolers may show some aspects of behaviors particularly those related to pro-social and cognitive areas. It also indicated that children from high educated environments demonstrated IL behaviors more than those coming from low educated environments. Finally, children coming from larger family size showed less IL behaviors than those coming from smaller ones. Results and implications are discussed.